FEASIBILITY LEVEL OF BEACH TOURISM OBJECTS IN SELATAN MALANG REGENCY, INDONESIA - Rima Karima; Rahel Situmorang; Anindita Ramadhani (Journal of Synergy Landscape, 2022)
Feasibility is a practical assessment by assessing the advantages and disadvantages possessed by a resource that is the object of the assessment, in this case, the beach tourism object. A beach tourism object is a place with an attractive value in a coastal area that functions as a place for recreation and land sports to visit. The area that became the unit of analysis in this study was 6 (six) beach tourism objects in Tambakrejo Village, Malang Regency. Tambakrejo Village, Sumbermanjing Wetan District, is a village that has the most beach tourism objects in Malang Regency. Malang Regency has the potential for coastal tourism that has not been managed optimally by the Malang Regency Government. The lack of budget for developing beach tourism objects in Malang Regency makes the condition of road access, supporting infrastructure, and facilities at beach tourism object inadequate. This study aimed to identify beach tourism objects' feasibility level in South Malang Regency. The method used in this study is the feasibility analysis of tourist objects and attractions using the scoring method. This study's results indicate that a feasible beach tourism object is Tamban Beach. Decent beach tourism objects are Sendiki Beach, Sendang Biru Beach, and Tiga Warna Beach, while Clungup Beach and Gatra Beach have a less feasible value